Atrial fibrillation recurrence after transcatheter ablation worsens left atrial strain. (25th November 2020) - Annunziata, R; Notaristefano, F; Spighi, L; Piraccini, S; Giuffre', G; Deluca, F; Bearzot, L; D'Ammando, M; Reccia, M.R; Verdecchia, P; Zingarini, G; Cavallini, C
Abstract: Introduction: Left atrial strain (LAs) shows correlation with atrial fibrosis and is a predictor of atrial fibrillation (AF) recurrence after transcatheter ablation. Little is known about LAs evolution after ablation. Purpose: We sought to evaluate the atrial function with echocardiographic strain before and 6 months after AF ablation. Methods: 65 consecutive patients undergoing radiofrequency or cryoballoon ablation for atrial fibrillation at our centre were enrolled. They underwent a transthoracic echocardiography before the procedure and at 6 months follow-up. 5 patients were excluded because of low quality images. Global left atrial strain during the reservoir phase (LASr) was calculated as a mean of the values obtained in 4 and 2 chamber apical view; the ventricular end-diastole was set as reference to allow the calculation both in patients in AF and sinus rhythm during the echocardiography. Recurrence was defined as any atrial arrhythmia episode lasting more than 30 seconds recorded on an EKG strip after the 3 months blanking period; all patients underwent a 24 hours EKG Holter after the blanking period to detect asymptomatic recurrence. Quality of life was assessed before the procedure and at follow-up with the EQ-5D-3L model. Results: At 6 months 14 patients (13%) had AF recurrence. Patients with recurrence (AF-R) had similar baseline characteristics compared to those without recurrence (AF-NR) but the former had a longer history of AF (39±53 vs 85±94 months, p=0, 018). LASr, LA volume and left ventricle ejection fraction (EF) were similar at baseline between groups. At follow-up LASr was significantly impaired in the AF-R group compared to AF-NR (14±6% vs 26±10% respectively, p<0, 0001) whereas LA volume, LV end systolic volume and EF remained similar. Compared to baseline LASr worsened in patients experiencing AF recurrence (22±11% vs 14±6%, p=0.016) and this finding was consistent also in patients in sinus rhythm during both examinations (29±8 vs 17±7, p=0, 005). Compared to baseline LASr (22±10% vs 26±10%, p=0.024), LV end-systolic volume (29±15 ml vs 22±6 ml, p=0, 006) and EF (51±9% vs 58±18%, p=0, 038) improved in the AF-NR group but the effect was driven mainly by patients restoring sinus rhythm. Both groups showed a significant improvement of the quality of life (55±23 vs 85±13, p<0, 0001 AF-NR; 63±17 vs 80±12, p=0, 012 AF-R). Conclusions: Atrial fibrillation recurrence after transcatheter ablation is associated with significant left atrial strain worsening which indicates disease progression and may predispose to further long-term recurrences whereas a successful ablation has a protective effect on atrial function. Funding Acknowledgement: Type of funding source: None